Wind Humanities: An Elemental Media Approach - Maximilian Hepach; Ryan Bishop; J. R. Carpenter; Jussi Parikka; Birgit Schneider (Media + Environment)
This article introduces wind humanities as a burgeoning field, exploring how wind shapes experience, reasoning, artistic and knowledge production. It positions wind as a medium, model, and lived experience, drawing on environmental humanities, media studies, and artistic practice to investigate wind's methodological, epistemological, and ontological implications for humanistic inquiry. The authors situate this emergent field within the broader environmental and elemental turn in the humanities and media studies, highlighting its connections to new materialism and its potential to transform our understanding of both wind and the elemental more broadly. They suggest a rich and evolving landscape of inquiry around wind, highlighting past work and introducing the ten contributions to this stream, which explore wind as media, model, and experience across military technology, volumetric poetry, a libretto, animacies, aesthetics, diffraction, environmental perception, risk communication, indigenous cosmologies, and energy infrastructure.